Strikes and Class Consciousness - Langford, Tom (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1994)
This article uses a classical Marxist framework to study the consciousness and action of inside postal workers in Hamilton, Ontario during and after their participation in the 1987 strike by the Canadian Union of Postal Workers (CUPW). At the time of the strike the Hamilton Local of CUPW was 58 per cent women; the article includes a discussion of the impact of gender processes on women worker's consciousness and action. It also deals with three more general issues. First, through a discussion of conceptual issues and the presentation of a multi-level theoretical model, I offer advice on how to proceed with empirical research on strikes and class consciousness. Second, the "culture of solidarity" portrayal of strikers, as developed by Rick Fantasia, is criticized for presenting an over-integrated view of the participation and consciousness of strikers. I argue that one need not romanticize striking workers in order to be optimistic about the political role of the contemporary working class. This optimism must recognize that in a macro context of politico-economic stability, only a minority of a striking workforce can be expected to experience an expansion of generalized class consciousness. Third, I suggest that Marxist political action in the 1990s should concentrate on the development of generalized class consciousness, especially workers' positive sense of class unity, through the organization of local worker solidarity networks.